"I'll Be There for You": Teen Parents' Coparenting Relationships. Issue 2 (April 2015) - Mollborn, Stefanie; Jacobs, Janet
<x xml:space="preserve">Abstract</x> Marriage promotion policy agendas have focused research attention on coparenting relationships, but little is known about coparenting among teen parents. Using qualitative interviews with 76 teen mothers and fathers supplemented with site observations at a school and clinic, the authors investigated coparenting relationships and those relationships' embeddedness in extended families and social institutions. They identified prevalent coparenting trajectories and analyzed individual‐, interaction‐, and institutional‐level influences on coparenting. Coparenting trajectories diverged depending on whether the couple stayed together and assumed traditionally gendered parenting roles. Participants perceived that coparenting relationships strongly shaped their current and future socioeconomic, emotional, and practical circumstances and their success at "being there" for their child. Extended families, institutions, and social programs often pushed teen parents apart, although many participants felt they needed a functional relationship with the other parent. Coparenting relationships, considered jointly with extended families and social institutions, are fundamental for understanding teen parenthood and shaping effective social policies.